Women, convents and divorce in early modern Spain - Intxaustegi Jauregi, Nere Jone (Avisos de Viena, 2025)
There are archival records of women in the Golden Age seeking divorce from their husbands while living in a convent, which may seem unusual today. So I am interested in exploring why a woman in the early modern period would enter a convent and seek a divorce from there. I present identities, different examples and motivations that help to understand this dynamic.